ANALISIS KEDUDUKAN DAN FUNGSI HIKAYAT RAJA BUDAK - Diana, Ani (JURNAL PESONA, 2015)
AbstractÂ Hikayat Raja Budak (HRB) is one of Malay literature in prose. Based on the content, HRB contains relevant high moral teaching current life. Besides that HRB reflected the custom which is existed of Malay kings of yore, especially the customs that inherited from Sriwijaya era. This study aims to describe the position and function of Hikayat Raja Budak. The methods of this research are using descriptive and analytical methods. Descriptive method was used to describe the data in the form of HRB manuscript. HRB manuscript that examined in this study was obtained from Perpustakaan Nasional Republik Indonesia (PNRI). Based on its position in Malay literature HRB can be classified in the Malay literary that influenced by Hindu-Islam transition. This classification based on the story that contains blend elements of Hinduism and Islam. The story function of HRB is for education, especially moral education, events preservation or applicable customs of ancient Malay kings, and also entertainment.Key Words: Position, Function, Malay Tale, Hikayat Raja Budak.